Chronic Stress Alters Spatial Representation and Bursting Patterns of Place Cells in Behaving Mice - Park, Mijeong; Kim, Chong-Hyun; Jo, Seon mi; Kim, Eun Joo; Rhim, Hyewhon; Lee, C. Justin; Kim, Jeansok J.; Cho, Jeiwon (NATURE PUBLISHING GROUP, 2015)
Chronic uncontrollable stress has been shown to produce various physiological alterations and impair mnemonic functions in the rodent hippocampus. Impacts on neuronal activities, however, have not been well investigated. The present study examined dorsal CA1 place cells to elucidate the computational changes associated with chronic stress effects on cognitive behaviors. After administering chronic restraint stress (CRS; 6 hours/day for >= 21 consecutive days) to adult male mice, several hippocampal characteristics were examined; i.e., spatial learning, in vitro synaptic plasticity, in vivo place cell recording, and western blot analysis to determine protein levels related to learning and memory. Behaviorally, CRS significantly impeded spatial learning but enhanced non-spatial cue learning on the Morris water maze. Physiologically, CRS reduced long-term potentiation (LTP) of Schaffer collateral/commisural-CA1 pathway, phospho-alpha CaMKII (alpha Ca2+/calmodulin-dependent protein kinase II) level in the hippocampus, and stability of spatial representation and the mean firing rates (FRs) of place cells. Moreover, the local cue-dependency of place fields was increased, and the intra-burst interval (IntraBI) between consecutive spikes within a burst was prolonged following CRS. These results extend the previous findings of stress impairing LTP and spatial learning to CRS modifying physical properties of spiking in place cells that contribute to changes in navigation and synaptic plasticity.